Octoblepharum pocsii (Calymperaceae), a recently described African moss species new to Laos and Asia - He, Si (Phytotaxa, 2014)
The genus Octoblepharum Hedwig (1801: 50), consisting of 18 accepted species, is mainly distributed in the tropical and subtropical regions of the world, with four species in Africa, one in Asia, and the majority of the species in the Neotropics; it is seldom found in temperate latitudes (Eddy 1990, Salazar-Allen 1991, Magill & Allen 2013).